2021
DOI: 10.15586/qas.v13i1.808
|View full text |Cite
|
Sign up to set email alerts
|

Producing high Fischer ratio peptides from milk protein and its application in infant formula milk powder

Abstract: Milk protein is beneficial for the health of infants and is mainly derived from bovine, sheep, goat or camel milk. High Fischer ratio peptides usually comprise two to nine amino acid residues. The ratio is computed as a molar ratio between branched-chain amino acids (BCAAs) over aromatic amino acids (AAAs) with various claimed health-promoting functions. In this Lilliput review, the classification and nutritional functions of milk proteins are discussed, the physiological functions and preparation methods of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Alterations to the secondary and tertiary structures of proteins caused by heat treatment may eliminate, disguise, or expose conformational epitopes, all of which profoundly affect allergenicity [ 244 , 245 ]. Furthermore, protein allergenicity may be chemically changed due to interactions between allergenic proteins and other components (such as sugar, oxidized lipids, and polyphenols).…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
“…Alterations to the secondary and tertiary structures of proteins caused by heat treatment may eliminate, disguise, or expose conformational epitopes, all of which profoundly affect allergenicity [ 244 , 245 ]. Furthermore, protein allergenicity may be chemically changed due to interactions between allergenic proteins and other components (such as sugar, oxidized lipids, and polyphenols).…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
“…Each type of protein has unique properties, which affect the texture and flavor of the final product. For example, soy protein has a slightly nutty flavor, and whey protein has a more neutral flavor (Shi and Li, 2021). Although protein-based fat replacement has some advantages over carbohydratebased fat replacement in terms of lowering both fat and cholesterol, calorie reduction, flavor enhancement, and health benefits, their high cost restrict their usage in the manufacture of dairy products (Kew et al, 2020;Yashini et al, 2019).…”
Section: Protein Co-productsmentioning
confidence: 99%
“…Studies demonstrated the antihypertensive effect of casokinins and lactokinins, casokinins contain high ACE inhibiting function and antihypertensive effects in casein hydrolysate C12 peptide (Selvaggi et al, 2014). Some other ACE inhibitory peptides found in goat milk, include C7 and C6 peptides, in addition to C12, and may add value to the antihypertensive effect of C12 peptides (Shi & Li, 2021).…”
Section: Health Benefits Of Goat Milk Proteinsmentioning
confidence: 99%